2017
DOI: 10.1186/s41606-016-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood of obstructive sleep apnea in people living with HIV in Cameroon – preliminary findings

Abstract: Background: Obstructive Sleep Apnea (OSA) has been observed to be common among people living with HIV/AIDS (PLWHA). Sleep scales can be used to screen patients at increased "risk" of OSA who can benefit from polysomnography. This study therefore sought to generate preliminary data on this often unattended complication of HIV Infection in Cameroon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
1
12
4
Order By: Relevance
“…In the current study a significant difference was not found between underlying diseases like diabetes, pulmonary, and cardiovascular diseases. In the study by Njoh et al .,[ 11 ] 43.6% of HIV-positive patients are classified in the high-risk group which is significantly higher than healthy individuals (14%). Furthermore, there are some other studies reporting a higher prevalence of sleep apnea among HIV-positive patients in comparison with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study a significant difference was not found between underlying diseases like diabetes, pulmonary, and cardiovascular diseases. In the study by Njoh et al .,[ 11 ] 43.6% of HIV-positive patients are classified in the high-risk group which is significantly higher than healthy individuals (14%). Furthermore, there are some other studies reporting a higher prevalence of sleep apnea among HIV-positive patients in comparison with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It can also disrupt the patient's adherence to treatment, leading to disease progression, making it a challenge in the HIV control program. [ 7 11 12 13 ] Several studies show that due to secondary opportunistic infections among HIV-positive patients, the appetite is reduced, which additionally results in weight loss. [ 9 10 ] Therefore, considering the impact of potential risk factors such as body mass index (BMI), studies suggested that BMI may not be associated with OSA among PLHIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cameroon, sleep studies are few [ 14 ], and to our knowledge, no study so far has been carried out to assess sleep in hypertensive participants. It was hence essential to conduct assessments of sleep patterns of hypertensive patients in Cameroon with the aid of clinician-friendly, readily-available, less costly and easy-to-use sleep questionnaires, in order to generate preliminary data on the likelihood (risk) of obstructive sleep patterns (and consequent daytime sleepiness) in patients with hypertension compared to normotensive participants from which further exploration, management and awareness-raising initiatives can be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to understand that antiretroviral therapy patients living with HIV suffer from specific types of sleep disorders. Based on previous studies, we found that sleep disorders among HIV-infected persons do not appear to have been comprehensively explored, but these studies have focused only on insomnia [ 9 ] or sleep apnea [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%